The implications of FASN in immune cell biology and related diseases - Yucai Xiao; Yonghong Yang; Huabao Xiong; Guanjun Dong (Cell Death and Disease, 2024)
Abstract Fatty acid metabolism, particularly fatty acid synthesis, is a very important cellular physiological process in which nutrients are used for energy storage and biofilm synthesis. As a key enzyme in the fatty acid metabolism, fatty acid synthase (FASN) is receiving increasing attention. Although previous studies on FASN have mainly focused on various malignancies, many studies have recently reported that FASN regulates the survival, differentiation, and function of various immune cells, and subsequently participates in the occurrence and development of immune-related diseases. However, few studies to date systematically summarized the function and molecular mechanisms of FASN in immune cell biology and related diseases. In this review, we discuss the regulatory effect of FASN on immune cells, and the progress in research on the implications of FASN in immune-related diseases. Understanding the function of FASN in immune cell biology and related diseases can offer insights into novel treatment strategies for clinical diseases.